Experimental study on gas and coal dust explosive overpressure and flame dynamic characteristics in an engineering-level test roadway - Niu, Yihui; Si, Rongjun; Li, Ziran; Wang, Lei; Huang, Zichao; Jia, Quansheng (Frontiers in Earth Science, 2023)
The continuous development of coal science and technology has made gas and coal dust explosion disasters an important factor that restricts efficient and intelligent coal mining, which seriously threatens the safe production process of coal mines. To explore the gas and coal dust explosive overpressure and flame propagation characteristics in an actual roadway, the dynamic characteristics of gas and coal dust mixed explosion propagation and evolution laws of explosion flames were investigated using an integrated explosion test system and a high-speed image acquisition system in an engineering-level test roadway with a length of about 700 m and a cross-sectional area of 7.2 m 2. Experimental results showed that the peak overpressure measured at each measuring point during the propagation process of explosion shock wave in the roadway did not rise or fall monotonously but fluctuated. The power of explosion shock wave was significantly strengthened by adding coal dust, while the flame propagation speed sharply increased in a certain zone, which generally showed a first increasing and then declining trend. In addition, the flame was blue white after the gas in the roadway was ignited, developed in an irregular shape, and ignited the surrounding combustible gas soon, which further ignited the coal dust under the combined action of pressure wave and flame front. In this case, the flame was deep yellow on the whole. The gas and coal dust explosion flame propagated along the longitudinal section above the roadway, and the flame propagated at an accelerated speed on the transverse section due to the disturbance of obstacles. The study results will provide an important theoretical basis for the R&D of technical active explosion suppression equipment in coal mines and the improvement in their installation technologies.